2009
DOI: 10.1186/1475-2875-8-234
|View full text |Cite
|
Sign up to set email alerts
|

Habitat stability and occurrences of malaria vector larvae in western Kenya highlands

Abstract: Background: Although the occurrence of malaria vector larvae in the valleys of western Kenya highlands is well documented, knowledge of larval habitats in the uphill sites is lacking. Given that most inhabitants of the highlands actually dwell in the uphill regions, it is important to develop understanding of mosquito breeding habitat stability in these sites in order to determine their potential for larval control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 25 publications
3
48
0
Order By: Relevance
“…However, those ponds with persisted water at the end of observational period were located close to permanent streams and waterlogged areas ( Figure 1 and Table 1). This is in agreement with the study of Himeidan et al (2009), who also found that longer-lived developmental habitats were located near streams and water sources in the eastern African highlands. In the same district, Mushinzimana et al (2006) made similar observations with more than 60% of positive habitats found within 50 metres from streams in both dry and rainy seasons.…”
Section: Pond Measurementssupporting
confidence: 93%
See 2 more Smart Citations
“…However, those ponds with persisted water at the end of observational period were located close to permanent streams and waterlogged areas ( Figure 1 and Table 1). This is in agreement with the study of Himeidan et al (2009), who also found that longer-lived developmental habitats were located near streams and water sources in the eastern African highlands. In the same district, Mushinzimana et al (2006) made similar observations with more than 60% of positive habitats found within 50 metres from streams in both dry and rainy seasons.…”
Section: Pond Measurementssupporting
confidence: 93%
“…This confirms that both habitat size and local hydrological conditions influence pond stability and within the same area, size might be the dominant factor , however, over a wider area, habitats location might be the key factor controlling its variability in stability. For instance, Himeidan et al (2009) found that the percentage of stable habitats was 48.76% and 80.79% for habitats located on top of the hills and near streams, respectively.…”
Section: Pond Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Anopheles funestus is associated with swamps and emergent vegetation and was more abundant during the dry seasons (Minakawa et al, 2005). Larval breeding habitats in the highlands are restricted to the valley bottoms (Munga et al, 2005) or to water bodies in hilltop plateaus in the highlands (Himeidan et al, 2009). The productivity of the habitats is affected by the quality of drainage, land cover and land use, stability of the habitats, temperature, predators and food availability.…”
Section: Larval Ecologymentioning
confidence: 99%
“…Understanding larval ecology is critical to implementation of larval sources management using environmental interventions and bio-larvicides. Larval habitat stability is a function of topography and proximity to rivers, stream and other stable water bodies (Himeidan et al, 2009). Open drainage channels in reclaimed valley bottoms were the most stable breeding habitats though paddles are the most productive but the least stable An.…”
Section: Larval Ecologymentioning
confidence: 99%